December 1949 Radioactive Iodine Christmas poster 1989 (Tufts Archival Research Center, 2017)
Poster for an exhibit staged in Seattle, Washington December, 1989. Sticky note attached to poster and removed prior to digitization reads "Poster from Dec. 1989 Photo Exhibit -- our first project."